An In Vitro Study Of The Effects Of Final Irrigation Protocols On A New Bioceramic Sealer (Journal of Pharmaceutical Negative Results, 2022)
Aim & Objective: The objective of this in vitro research was to assess how final irrigation techniques affected the apical micro leakageof a bioceramic sealer.Materials and Methods: To standardise the canal length, sixty single-rooted mandibular premolar teeth that had been removed were obtained and decoronated. The working length of the root canals was established after accessing them. NiTi rotary files were used to prepare the root canals. Based on the final watering strategy, samples were randomly split into three groups, totaling 20 N.Group1. 5 ml of 17% EDTA for 1min followed by 5ml of 5%NaOCl, 5ml Distilled water. Group2. 5ml of Q MIX 2 in 1, 5ml Distilledwater. Group3. 5ml of 2% CHLORHEXIDINE, 5ml Distilled water. Using a single-cone approach and a novel bioceramic sealant, the canals were obturated. To enable the sealer to fully set, all roots were put in 100% humidity and incubated at 37 oC for 24 hours. After the root surfaces had dried, two coats of nail polish had been applied, with the exception of the 2mm at the tip, which had been submerged in 1% methelyne blue for 72 hours. After that, the samples were longitudinally sectioned, and dye penetration was examined using a stereomicroscope (10xmagnification). Using the Image Pro Express 6 software, the maximum apical dye penetration leakage was determined. One-way ANOVA and Tukey's HSD post hoc analysis were used to statistically analyse the data.Results: Of all the experimental groups, Group 1 had the least percentage of apical leakage. Between each group, there were significant variations in the degree of apical micro leakage (P 0.001).Conclusion: Within the constraints of this investigation, it was shown that when Bioroot RCS was used as the sealer, final irrigation with 17% EDTA followed by 5% sodium hypochlorite demonstrated the least degree of apical leakage.